PHARMACEUTICAL STUDY OF DIFFERENT SAMPLES OF AGASTYA HARITAKI - Agrawal Sachin; Prasad Anjali Baijnath; Mundhra Varsha; Rathi Rajesh; Rao. K Shankar (International Journal of Applied Ayurved Research, 2018)
Avaleha kalpana is in practice since ancient days. It has many benefits over basic Ayurvedic pharmaceutical dosage form viz. easy administration, pleasant and agreeable taste, palatable to all age groups, longer shelf life, higher efficacy, nutritive values and is safe in use. Avaleha is specifically indicated for disease of upper respiratory tract like Kasa (Cough), Peenasa (Sinusitis), Kshaya (Phthisis) Krimi (Worm infestation), Arsha (hemorrhoids), Swasa (Asthma/ dysponea) and Agnimandya (Digestive impairment). Avaleha is a secondary preparation (Semisolid preparation of drugs) also known as leha Kalpana generally contains aqueous media, of drug i.e. Kwatha, Swarasa etc; a sweet substance, oleaginous substances (Sneha dravya) and few adjuvant (Prakshepa).